Health related quality of life among Iraqi immigrants settled in Malaysia - Daher Thaaer M; Ibrahim Hisham S; Daher Aqil M; Anbori Ali (BMC, 2011)
Abstract Background Migrants everywhere face several demands for health and maintaining good health and quality of life could be challenging. Iraqis are the second largest refugee group that has sought refuge in the recent years, yet little is known about their health related quality of life (HRQOL). The study aims at assessing the HRQOL among Iraqis living in Malaysia. Methods A self-administered Arabic version of Sf-36 questionnaire was distributed among 300 Iraqi migrants in Malaysia. The questionnaire taps eight concepts of physical and mental health to assess the HRQOL. Univariate analysis was performed for group analysis (t test, ANOVA) and Multiple Linear Regression was used to control for confounding effects. Results Two hundred and fifty three participants ranging in age from 18 to 67 years (Mean = 33.6) returned the completed questionnaire. The majority was males (60.1%) and more than half of the respondents (59.5%) were married. Less than half (45.4%) and about a quarter (25.9%) reported bachelor degree and secondary school education respectively and the remaining 28.7% had either a master or a PhD degree. Univariate analysis showed that the HRQOL scores among male immigrants were found to be higher than those of females in physical function (80.0 vs. 73.5), general health (72.5 vs. 60.7) and bodily pain (87.9 vs. 72.5) subscales. The youngest age group had significantly higher physical function (79.32) and lower mental health scores (57.62). The mean score of physical component summary was higher than the mental component summary mean score (70.22 vs. 63.34). Stepwise multiple linear regression, revealed that gender was significantly associated with physical component summary (β = - 6.06, p = 0.007) and marital status was associated with mental component summary (β = 7.08, p = 0.003). Conclusions From the data it appears that Iraqi immigrants living in Malaysia have HRQOL scores that might be considered to indicate a relatively moderate HRQOL. The HRQOL is significantly affected by gender and marital status. Further studies are needed to explore determinants of HRQOL consequent to immigration. The findings could be worthy of further exploration.